Elucidating the Mechanism of Action of Umami-Enhancing Peptides Derived from Chicken Based on Molecular Simulation - ZHANG Jingcheng, HE Wei, LIANG Li, ZHANG Yuyu (Shipin Kexue)
To investigate the mechanism of action of umami-enhancing peptides, molecular simulation and sensory evaluation were employed to analyze the umami-enhancing effects of three peptides derived from chicken: LPLQD, DGGRYY, and DEAGPSIVH, the molecular mechanism of umami-enhancing peptide-glutamic acid-taste receptor interaction and the dynamic binding process. The results indicated that all three umami-enhancing peptides exhibited good water solubility and non-toxicity and had an additive effect on the umami taste of 0.35% glutamic acid solution. Molecular docking results revealed that the presence of umami-enhancing peptides greatly enhanced the interactions between the ligand system and the taste receptor type 1 (T1R1) including electrostatic interaction, hydrophobic interaction, and hydrogen bonding interaction, thereby leading to enhanced binding stability. Furthermore, molecular dynamic simulations disclosed that the venus flytrap (VFT) domain in the T1R1 receptors was relatively stable, while the cysteine-rich domain exhibited significant spatial fluctuations. Statistics of hydrogen bonds indicated that the addition of umami-enhancing peptides to the ligand system enhanced the hydrogen bonding interaction and consequently binding intensity between ligands and receptors. By analyzing the frontier molecular orbitals, serine, tyrosine, glutamine, arginine, and histidine residues were identified as active sites in the peptides that contributed to the binding with T1R1. The above results provide theoretical support for understanding the umami-enhancing mechanism of peptides and for the development of new umami enhancers.